2021
DOI: 10.1007/s10903-021-01230-7
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Leads to Dramatic Changes in the Food Retail Environment in New York City: May–July 2020

Abstract: A systematic assessment of the effect of COVID-19 on the food retail environment-an important determinant of health-has not been conducted. Our objective was to assess the impact of COVID-19 on closures of restaurants, food retail stores, and fresh produce vendors in New York City (NYC). We conducted a cross-sectional study following the peak of COVID-19 in six neighborhoods in NYC. Two Chinese ethnic neighborhoods and four higher/lower resourced comparison neighborhoods were selected a priori based on 14 soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…A summary of the key findings (i.e., closures by neighborhood) has been described elsewhere [ 35 ]. In this paper, we present data relating to the Summer 2020 data collection phase in three Manhattan neighborhoods - UES, East Harlem, and Chinatown – and three Brooklyn neighborhoods – Park Slope, Brownsville, and Sunset Park.…”
Section: Resultsmentioning
confidence: 99%
“…A summary of the key findings (i.e., closures by neighborhood) has been described elsewhere [ 35 ]. In this paper, we present data relating to the Summer 2020 data collection phase in three Manhattan neighborhoods - UES, East Harlem, and Chinatown – and three Brooklyn neighborhoods – Park Slope, Brownsville, and Sunset Park.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this paper support the findings of earlier research on food outlet closure during the pandemic. Yi et al (2021) found a vanishing food infrastructure in their study of New York neighborhoods. Like us, they found the highest closures amongst restaurants and small grocery stores.…”
Section: Discussionmentioning
confidence: 96%
“…Compared to other racial/ethnic groups, Asians/Asian Americans had the highest percentage decline in the number of frontline workers [ 28 ]. Food businesses in ethnic Chinese neighborhoods closed at a higher rate compared to food businesses in other neighborhoods [ 29 ]. Additionally, Asian/Asian American-owned businesses faced obstacles in obtaining Payment Protection Program (PPP) loans, meant to support small businesses and prevent closing, that resulted in many not receiving assistance [ 5 , 26 ].…”
Section: Introductionmentioning
confidence: 99%